Identifying Ecological Security Patterns Based on Ecosystem Services Is a Significative Practice for Sustainable Development in Southwest China - Su, Xukun; Shen, Yu; Xiao, Yi; Liu, Yuqing; Cheng, Hao; Wan, Lingfan; Zhou, Su; Yang, Murong; Wang, Qiusheng; Liu, Guohua (Frontiers in Ecology and Evolution, 2022)
Southwest China, which is rich in biodiversity and wide range of ecosystem services (ESs), is a strong support for local human well-being. This area is also one of the key components of ecological security shelter (ESS) for national ecological security and biodiversity conservation. Due to the combination of man-made and natural factors, Southwest China has suffered serious ecological degradation to directly threat ecological security which refers to health status of ecosystems and ESs functions. Mapping ESs-based ecological security patterns (ESPs) is essential for designing conservation strategies that suitably combine regional environment conservation with sustainable utilization. We used the InVEST (Integrated Valuation of Ecosystem Services and Tradeoffs Tool) model to identify ecological conservation priority areas which integrated ecological sensitivity (soil erosion sensitivity, rock desertification sensitivity, landslide sensitivity, debris flow sensitivity and freezing-thawing erosion sensitivity), ecological risk (drought risk, natural disaster risk and socio-economic risk) and ecological conservation importance (soil conservation, water conservation and biodiversity conservation importance). In this research, we summarized a new designing framework of the ESs-based ESPs. We divided the study area into 2 zones and 4 belts included that: (A) alpine steppe and wetland zone, (B) Hengduan Mountain zone, (C) northern shelter belt (Daba-Micang Mountain), (D) central shelter belt (Wumeng-Wuling Mountain), (E) southern shelter belt (southern border of China) and (F) southwestern shelter belt (eastern Himalayas Mountain). Identifying distributions of the ESs-based ESPs has practical significance to improve local human well-being and to maintain sustainable development of natural-social ecosystems in Southwest China. Furthermore, the ESs-based ESPs is necessary to make rationalizing plans by local administrations on balancing natural resources conservation and utilization, so that policy-makers can make targeted prevention and control measures to limit the development of natural resources excessive consumption and ecological damages, which is worth promoting.